Recent Advances in Canine Medicine - Eduardo Fonseca-Alves, Carlos (Veterinary Medicine and Science, 2023)
Veterinary medicine has grown in importance in recent years as dogs have become even more important in human society. For many years, dogs have served as protectors, companions, and even workers. The close relationship between dogs and humans has created a need for specific techniques and interventions for their care. Advances in canine medicine have resulted in dogs living longer, healthier lives. However, dogs are still susceptible to diseases and illnesses. This book provides a comprehensive overview of canine medicine and advances in the diagnosis and treatment of infectious, degenerative, and immunological diseases, cancer, and much more.